Vessel Preparation Is Essential to Optimize Endovascular Therapy of Infrainguinal Lesions - Saucy, François; Probst, Hervé; Trunfio, Rafael (Frontiers in Cardiovascular Medicine, 2020)
Symptomatic peripheral arterial disease management involves medical treatment and interventional procedures. Intermittent claudication and critical limb threatened ischemia (CLTI) should be individually considered with specific outcomes and procedures. When intervention is required, an endovascular approach is usually the first-line option. Plain balloon angioplasty was previously used to dilate clinically significant femoropopliteal lesions with variable results. However, over recent years, the use of self-expanding nitinol stents has enabled treatment of long lesions, yielding significantly improved clinical results. Drug-eluting technology has also exhibited a capacity to limit in-stent restenosis and to drive target revascularization. Nevertheless, calcifications and elastic recoil of the arterial wall remain risk factors for early restenosis and failure. Therefore, vessel preparation using specific devices is required to modify vessel compliance and debulk obstructive calcification. In this short review, we provide an overview of the options for gaining lumen before stenting or dilation using drug-coated balloons.